The distribution of failure in medical and health insurance claim: the implications of multiple binary logistic regressions - Norimah Rambeli @ Ramli (Tanjung Malim, 2023)
The distribution of failure in medical and health insurance claim: the implications of multiple binary logistic regressions by Norimah Rambeli @ Ramli